California Maritime Academy - Pacific Marine Review (Pacific Marine Review)
The California Maritime Academy was established by legislation enacted in 1929 for the purpose of training young men for service as officers in the United States Merchant Marine. At the present time, the length of the course is two years and graduates are awarded licenses as Third Mates. Third Assistant Engineers, a commission as Ensign in the United States Maritime Service, and a commission as Ensign in the United States Naval Reserve. For new incoming classes the length of the course Will be three years, and graduates will be awarded a Bachelor of Science Degree and will probably receive a license as Second Mate or Second Assistant Engineer instead of Third Mate or Third Assistant Engineer, in addition to their commissions in the United States Naval Reserve and United States Maritime Service.